Science, culture, and care in laboratory animal research: interdisciplinary perspectives on the history and future of the 3Rs - Davies, Gail; Greenhough, Beth J.; Hobson-West, Pru; Kirk, Robert G.W. (Sage, 2018)
The principles of the 3Rs—replacement, refinement, and reduction—strongly shape discussion of methods for performing more humane animal research and the regulation of this contested area of technoscience. This special issue looks back to the origins of the 3Rs principles through five papers that explore how it is enacted and challenged in practice and that develop critical considerations about its future. Three themes connect the papers in this special issue. These are (1) the multiplicity of roles enacted by those who use and care for animals in research, (2) the distribution of “feelings that matter” across species and spaces of laboratory animal practice, and (3) the growing importance of “cultures of care” in animal research.